Source selection problem of competitive power plants under government intervention: A game theory approach - Reza Mahmoudi; Ashkan Hafezalkotob; Ahmad Makui (Journal of Industrial Engineering International, 2014)
Pollution and environmental protection in the present century are extremely significant global problems. Power plants as the largest pollution emitting industry have been the cause of a great deal of scientific researches. The fuel or source type used to generate electricity by the power plants plays an important role in the amount of pollution produced. Governments should take visible actions to promote green fuel. These actions are often called the governmental financial interventions that include legislations such as green subsidiaries and taxes. In this paper, by considering the government role in the competition of two power plants, we propose a game theoretical model that will help the government to determine the optimal taxes and subsidies. The numerical examples demonstrate how government could intervene in a competitive market of electricity to achieve the environmental objectives and how power plants maximize their utilities in each energy source. The results also reveal that the government's taxes and subsidiaries effectively influence the selected fuel types of power plants in the competitive market.
Keywords: 650; Game theory; Green electricity; Power plant; Bertrand game; Government intervention; Source selection